If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 = 8x + -1 Reorder the terms: 9 + 3x = 8x + -1 Reorder the terms: 9 + 3x = -1 + 8x Solving 9 + 3x = -1 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9 + 3x + -8x = -1 + 8x + -8x Combine like terms: 3x + -8x = -5x 9 + -5x = -1 + 8x + -8x Combine like terms: 8x + -8x = 0 9 + -5x = -1 + 0 9 + -5x = -1 Add '-9' to each side of the equation. 9 + -9 + -5x = -1 + -9 Combine like terms: 9 + -9 = 0 0 + -5x = -1 + -9 -5x = -1 + -9 Combine like terms: -1 + -9 = -10 -5x = -10 Divide each side by '-5'. x = 2 Simplifying x = 2
| 115=3-4(5x-8) | | 54-5x=22x+15 | | 3y-18=2y+5 | | -6R+13=2R-11 | | 196=7(3+5n) | | (3n-6)12=(-3)12 | | x+28=3x+14 | | 215+p-1001=9412 | | 4x-2x=-5x-1 | | -6/0.666666666667 | | x-7+7=7 | | 336=8(6a-6) | | 8-2x=4x+26 | | -2.8=4b | | x+x+(x+84)=180 | | 2(4+8m)=88 | | 2W-31=-9W+24 | | x-x-x-x=20 | | 5z+16=4z+14 | | 8x+2y=42 | | -4(-1+4v)=116 | | 7/4q-2=-5 | | -6+.25w=-4 | | 6(2+3x)=84 | | 4(x+1)=-16 | | -9=10-3(x+1)+11 | | -(4y+3)-(-3y-8)=-3equation | | .25b=-5 | | -1/2=-6/18h | | X-3y=5.4 | | -2p+9=13 | | -6(1-2x)=-90 |